2011
DOI: 10.1111/j.1365-2095.2010.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a mixture of meat and bone meal, poultry by-product meal, blood meal and corn gluten meal as a replacement for fish meal in practical diets of Pacific white shrimp Litopenaeus vannamei at two dietary protein levels

Abstract: A 6‐week feeding trial was carried out in glass tanks to determine the effects of partial replacement of fish meal (FM) with a combination of meat and bone meal (MBM), poultry by‐product meal (PBM), blood meal (BM) and corn gluten meal (CGM) in practical diets on the growth, nutrient digestibility and body composition of Pacific white shrimp. Six practical diets were formulated, containing two levels of crude protein (CP) (330 and 380 g kg−1) and similar crude lipid (CL) levels. For the 330 g kg−1 dietary prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
56
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 60 publications
(157 reference statements)
12
56
2
1
Order By: Relevance
“…The observation for growth performance also showed that up to 33% of the FM in a practical diet for whiteleg shrimp, reared in biofloc system, could be effectively substituted by the soybean meal (SBM). Previously, numerous studies have been conducted to evaluate the suitability of various feed ingredients as alternative protein sources for FM; as partial or even total replacement of FM by plant ingredients in the diet of L. vannamei has been reported by several authors (Amaya et al 2007;Suárez et al 2009;Olmos et al 2011;Ye et al 2011;Liu et al 2012;Yue et al 2012;Gu et al 2013;Sá et al 2013;Sookying et al 2013;Kuhn et al 2016;Xie et al 2016). In the present study, application of methionine and lysine in the diet did not significantly influence the growth performance.…”
Section: Discussionsupporting
confidence: 52%
“…The observation for growth performance also showed that up to 33% of the FM in a practical diet for whiteleg shrimp, reared in biofloc system, could be effectively substituted by the soybean meal (SBM). Previously, numerous studies have been conducted to evaluate the suitability of various feed ingredients as alternative protein sources for FM; as partial or even total replacement of FM by plant ingredients in the diet of L. vannamei has been reported by several authors (Amaya et al 2007;Suárez et al 2009;Olmos et al 2011;Ye et al 2011;Liu et al 2012;Yue et al 2012;Gu et al 2013;Sá et al 2013;Sookying et al 2013;Kuhn et al 2016;Xie et al 2016). In the present study, application of methionine and lysine in the diet did not significantly influence the growth performance.…”
Section: Discussionsupporting
confidence: 52%
“…Myer et al (1990) evaluated scallop viscera silage as a high-protein feedstuff for growing swine, confirming marine byproducts are suitable sources of nutrients for animal feeds. Squid viscera meal is a good attractant and growth enhancer in shrimp diets (Ye et al, 2011;Liu et al, 2012). Due to the high lipid content found here in giant squid viscera (204 g/kg), this raw material could be used to obtain oil rich in HUFA, specially DHA, EPA and ARA either for human consumption or to replace fish oil in animal diets.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary protein accounts for the majority of the content and expense of shrimp feed (Shiau et al ; Córdova‐Murueta and García‐Carreño ), which typically comprises fish and soybean meals. Due to the high cost of fish meal, a number of alternate protein sources have been examined over the years (Davis and Arnold ; Amaya et al ; Ye et al ). Cottonseed meal has several benefits, as it is a plant‐based material that is high in protein, less expensive than fishmeal, and generally understood to be free of heavy metals.…”
mentioning
confidence: 99%